Tungsten is utilized for lactate consumption and SCFA production by a dominant human gut microbe Eubacterium limosum - Saisuki Putumbaka; Gerrit J. Schut; Michael P. Thorgersen; Farris L. Poole; Nana Shao; Dmitry A. Rodionov; Michael W. W. Adams (Proceedings of the National Academy of Sciences, 2025)
Eubacterium limosum is a dominant member of the human gut microbiome and produces short-chain fatty acids (SCFAs). These promote immune system function and inhibit inflammation, making this microbe important for human health. Lactate is a primary source of gut SCFAs but its utilization by E. limosum has not been explored. We show that E. limosum growing on lactate takes up added tungstate rather than molybdate and produces the SCFAs acetate and butyrate, but not propionate. The genes encoding an electron bifurcating, tungsten-containing oxidoreductase (WOR1) and a tungsten-containing formate dehydrogenase (FDH), along with an electron bifurcating lactate dehydrogenase (LCT), lactate permease, and enzymes of the propanediol pathway, are all up-regulated on lactate compared to growth on glucose. Lactate metabolism is controlled by a GntR-family repressor (LctR) and two global regulators, Rex and CcpA, where Rex in part controls W storage and tungstopyranopterin (Tuco) biosynthesis. Tuco-dependent riboswitches, along with CcpA, also control two iron transporters, consistent with the increased iron demand for many iron-containing enzymes, including WOR1 and FDH, involved in SCFA production. From intracellular aldehyde concentrations and the substrate specificity of WOR1, we propose that WOR1 is involved in detoxifying acetaldehyde produced during lactate degradation. Lactate to SCFA conversion by E. limosum is clearly highly tungstocentric and tungsten might be an overlooked micronutrient in the human microbiome and in overall human health.